Formation of an Organizational and Economic Mechanism for Ensuring the Economic Sustainability of the Enterprise - Ivaniuk Uliana V.; Mykyta Nazariy O. (Bìznes Inform, 2025)
The article discusses aspects of effective management of finances and economics of enterprises. In other words, the main aspects are studied in the light of the formation and strengthening of the economic sustainability of enterprises and organizations from the position of the ability to attract, rationally distribute and effectively use resources, as well as to ensure stable and effective activities over a long period of time. These issues are of great importance in conditions of significant instability and economic chaos, caused by the critically negative consequences of the great war that is taking place in Ukraine. The aim of the article is to improve existing and form new methodological and applied provisions on the formation of an organizational and economic mechanism for ensuring the economic stability of enterprises in conditions of turbulence. It is shown that it involves the creation of a superstructure responsible for the development of a management system for economic sustainability and strategic development of the enterprise, when the organizational unit is responsible for the organization and management of processes, and the economic part of the mechanism is aimed at stimulating the achievement of goals and protecting the economic interests of participants in the system of economic sustainability of business. It is argued that the management contour of the organizational and economic mechanism consists of the aim, objectives, principles, methods, functions, tools, conceptions, environment of resource formation and control. It is proved that it is important to direct the tools of the organizational and economic mechanism for ensuring the economic stability of domestic enterprises in turbulent conditions to ensuring financial and economic stability and solvency, economic efficiency of management, and the growth and implementation of the enterprise's competitive advantages. The main principles of forming and implementing an organizational and economic mechanism for ensuring the economic sustainability of an enterprise have been determined. It is argued that the prospects of further research in this area should be directed towards a more thorough content filling of the characteristics of each of the elements of the organizational and economic mechanism for ensuring the economic sustainability of enterprises and organizations.